2016
DOI: 10.1037/xlm0000219
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating working memory updating and automatic updating: The reference-back paradigm.

Abstract: Working memory (WM) updating is a controlled process through which relevant information in the environment is selected to enter the gate to WM and substitute its contents. We suggest that there is also an automatic form of updating, which influences performance in many tasks and is primarily manifested in reaction time sequential effects. The goal of the present study was to dissociate WM updating and automatic updating, characterize the nature of these operations and identify the memory system responsible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(95 citation statements)
references
References 93 publications
(130 reference statements)
7
88
0
Order By: Relevance
“…Hence, the gate over WM should be closed in these trials. Previous results using this paradigm 50, 51 have demonstrated that (a) performance in reference trials is slower than in comparison trials, supporting the additional updating process required in the former, and (b) switching between the two trial-types is associated with an additional cost, reflecting the time taken to open or close the gate to WM 52, 53 .
Figure 1The reference-back task. Trials with a red frame are reference trials, and trials with a blue frame are comparison trials (see main text for details).
…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Hence, the gate over WM should be closed in these trials. Previous results using this paradigm 50, 51 have demonstrated that (a) performance in reference trials is slower than in comparison trials, supporting the additional updating process required in the former, and (b) switching between the two trial-types is associated with an additional cost, reflecting the time taken to open or close the gate to WM 52, 53 .
Figure 1The reference-back task. Trials with a red frame are reference trials, and trials with a blue frame are comparison trials (see main text for details).
…”
Section: Introductionmentioning
confidence: 73%
“…Inspired by the PBWM model and our previous results 50, 51 and under the assumption that the ebEBR reflects phasic DA activity, we predicted that WM updating and gate opening would be associated with an increase in the ebEBR. Gate closing would not be accompanied by an increase in the ebEBR because, as implied in the model, gate closing is the default state of the gate and does not require phasic DA.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The aim of the current study was to shed light on the involvement of DA in gating and WM updating, by examining task demand-related changes in eye-blink rate during performance on the reference back task 50,51 . The reference-back is a novel paradigm which allows separation of processes related to working memory updating from processes related to gate opening and closing.…”
Section: Introductionmentioning
confidence: 99%
“…Although there were no significant changes in neurophysiological measures after controlling for multiple comparisons, we found weak evidence that the intervention increased the P2 ERP amplitude. The P2 component has been linked to attentional processes (Kemp et al, 2006;Lijffijt et al, 2009;Luu et al, 2014;Yuan et al, 2016;Vilà-Balló et al, 2018)), whereas P3 is associated with higher-order cognitive functions such as target identification and categorisation (Friedman et al, 2001;Kok, 2001;Rac-Lubashevsky & Kessler, 2016). McEvoy et al (1998) systematically investigated the impact of working memory load and practice effects, and similarly observed changes in P2, but not P3, amplitude.…”
Section: Discussionmentioning
confidence: 99%